Influência da transmissão de luz através de pinos de fibra na microdureza e resistência adesiva do cimento - Luis Fernando Morgan dos Santos Alves (2011)
The aim of this study was to correlate the amount (Article 1) and influence of the transmission of light through fiber posts in microhardness (KHN) and bond strength (BS) (Article 2) in a dual self-etch resin cement. Four posts of different types and manufacturers for quantitative analysis were used. For KHN and BS five also deifferent types and manufacturers represented a test group. For the quantitative analysis of the KHN, a metal matrix was developed to simulate the radial positioning of the cement after the process of cementation. Three different depths were evaluated. The resistance to displacement, which will provide data of BS was performed using bovine incisors. For this test, after cementation, cross sections of the root portion of teeth in space of the post originated 1mm discs. The values were statistically analyzedby ANOVA and Tukey's at 95% confidence (P <0.05) for quantitative analysis of the radial light transmission, KHN and BS. Statistical analysis of the amount of light energy transmitted showed that it depends on the type of post and it reduces with increasing depth. To KHN, the resultsshowed no statistical differences for the different posts and thirds. For BS, when the thirds were summed, a translucent post showed the highest values. The comparative analysis between the thirds of each post also showed statistically significant differences, while comparisons of thesame post-thirds did not show any differences.